Thermodynamic analysis of aging - Swati Sinha. (2009)
Aging is the accumulation of changes in an organism. Numerous theories have been proposed to understand mechanism of aging. External environment factors, genomic component, somatic mutation, harmful effects of free radicals, decline of the immune response, deficiency in the endocrine system, accumulation of glycosylation and products, decreasing amount of heat-shock proteins and telomere shortening are thought to be related to aging. In this analysis the changing in the entropy (∆S), which is a measure of the disorder in a system, is evaluated to gain insights into the ageing of the extra-cellular matrix of tail tendons from C57BL6 mice as our animal model. Here, ∆S is modeled by the free expansion of collagen within the extracellular matrix of the tendons (between two age points) for reversible isothermal changes; this yields ∆S as a function of the ratio of fractional cross-sectional areas of collagen. Transmission electron micrographs of C57BL6 mouse tail tendons has been analysed to obtain the fractional cross-sectional area at age groups 1.6, 1.9, 2.6, 4.0, 11.5, 23.0, 29 and 31.5 months; the data was used to determine ∆S from the model. The results revealed that ∆S varies sinusoidally with age. The results obtained have been used to explain the change in entropy due to the collagen fibril assembly during fibrillogenesis.